An Analysis of Students’ Error in Pronouncing Dental Fricative Consonant [/ð/, /θ/] - Tahniah Eldika; Yetty Zainil (Universitas Negeri Padang, 2022)
This research was conducted to measure the students’ ability, to find out the types of error and its cause in pronouncing English dental fricative consonants produced by students’ of 2020 class at the English education program of Universitas Negeri Padang. This research was design using descriptive quantitative method. In this study, the researcher focused on the second-year English education students from K2-K5 class who had taken phonetic and phonology class. There are 30 students as the sample of this study. To collect the data, pronunciation test and Stimulated Recall Interview were used as the instrument where students’ voices were being recorded and being transcript. The findings of this study were students’ ability in pronouncing dental fricative consonants was fair with the percentage of 60%. The dominant type of error that happened in this study was misformation with 89,21% or 645 error out of 723 error. While for the cause of pronunciation error, based on the interview, the dominant reason was ineffectiveness of online learning due to Covid-19 pandemic.